Nanosecond pulse effectively ablated hepatocellular carcinoma with alterations in the gut microbiome and serum metabolites - Zou, Yawen; Sun, Ying; Chen, Xinhua; Hong, Liangjie; Dong, Gang; Bai, Xiwen; Wang, Haiyu; Rao, Benchen; Ren, Zhigang; Yu, Zujiang (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death in the world. Nanosecond pulsed electric fields (nsPEFs) have emerged as a new treatment for cancer. This study aims to identify the effectiveness of nsPEFs in the treatment of HCC and analyze the alterations in the gut microbiome and serum metabonomics after ablation. Methods: C57BL/6 mice were randomly divided into three groups: healthy control mice (n = 10), HCC mice (n = 10), and nsPEF-treated HCC mice (n = 23). Hep1-6 cell lines were used to establish the HCC model in situ. Histopathological staining was performed on tumor tissues. The gut microbiome was analyzed by 16S rRNA sequencing. Serum metabolites were analyzed by liquid chromatography–mass spectrometry (LC-MS) metabolomic analysis. Spearman’s correlation analysis was carried out to analyze the correlation between the gut microbiome and serum metabonomics. Results: The fluorescence image showed that nsPEFs were significantly effective. Histopathological staining identified nuclear pyknosis and cell necrosis in the nsPEF group. The expression of CD34, PCNA, and VEGF decreased significantly in the nsPEF group. Compared with normal mice, the gut microbiome diversity of HCC mice was increased. Eight genera including Alistipes and Muribaculaceae were enriched in the HCC group. Inversely, these genera decreased in the nsPEF group. LC-MS analysis confirmed that there were significant differences in serum metabolism among the three groups. Correlation analysis showed crucial relationships between the gut microbiome and serum metabolites that are involved in nsPEF ablation of HCC. Conclusion: As a new minimally invasive treatment for tumor ablation, nsPEFs have an excellent ablation effect. The alterations in the gut microbiome and serum metabolites may participate in the prognosis of HCC ablation.